Porous composite diaphragm, preparation method thereof and secondary battery

By introducing side chain cyano and carbonyl copolymers and double-scale pore structures into the separator coating, the problems of insufficient adhesion and poor lithium ion conductivity in traditional separators in high-silicon oxygen/carbon system batteries are solved, and efficient lithium ion transmission and battery performance improvement are achieved.

CN120261919AActive Publication Date: 2025-07-04NINGDE ZHUOGAO NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510712329.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-07-04
Estimated Expiration
2045-05-30

AI Technical Summary

Technical Problem

Traditional separators have caused the electrode sheet and separator to be broken due to changes in electrode material volume in high-silicon oxygen/carbon system batteries, and the internal resistance of the battery increases, and the swelling is obvious in strong polar electrolytes, which affects the interface stability and adhesion force, making it difficult to meet the needs of high-speed batteries.

Method used

A porous composite separator is used, and the coating contains copolymers with cyano groups and carbonyl groups on the side chains to form an intermolecular interaction network, combining pore structures with different pore sizes to improve lithium ion conductivity and pole sheet bonding performance.

Benefits of technology

The bonding performance between the diaphragm and the electrode sheet is improved, the lithium ion conductivity, the cycle stability and rate performance of the battery are improved, and the liquid retention ability under high pressure and high viscosity is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120261919A_ABST
    Figure CN120261919A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a porous composite diaphragm, a preparation method thereof and a secondary battery. The porous composite diaphragm comprises a base membrane, a first coating and a second coating, the first coating and the second coating are oppositely arranged on the two surfaces of the base film; the first coating layer and the second coating layer comprise a copolymer containing a first monomer unit and a second monomer unit; the first monomer unit contains a cyano group on a side chain, and the second monomer unit contains a carbonyl group on a side chain; in the copolymer, the molar ratio of the second monomer unit is 1-20%; the first coating and the second coating comprise skeleton structures and first-class pore structures formed between the skeleton structures, and second-class pore structures are formed on bodies of the skeleton structures; and the average pore diameter of the first-type pore structure is greater than that of the second-type pore structure. According to the porous composite diaphragm, the lithium ion conductivity can be improved while the bonding performance with a pole piece is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a porous composite separator, a preparation method thereof, and a secondary battery. Background Art

[0002] With the rapid development of high-energy density, large-capacity and high-rate lithium battery systems, the performance requirements for key materials (including positive and negative electrodes, separators, and electrolytes) are becoming increasingly stringent. As a bridge between the positive and negative electrodes, the separator has an important impact on lithium-ion transmission. In commercial production, the separator surface is usually coated with a polyvinylidene fluoride (PVDF) adhesive layer, and this design has multiple advantages: First, PVDF can effectively maintain the structural integrity of the electrode / separator interface by virtue of its excellent thermal stability, chemical resistance, strong wear resistance, and strong impact resistance; Second, in the semi-crystalline structure of PVDF, the crystalline regions provide mechanical support, and the amorphous regions provide adhesiveness and lithium-ion conductivity. By optimizing the molecular weight and crystallinity of PVDF, the adhesion performance can be regulated, etc.

[0003] However, with the rapid development of high-rate battery systems, traditional separators are facing severe challenges. In high-silica-oxygen / carbon system batteries, the electrode materials have large volume changes during cycling, and it is easy for the electrode sheets and the separator to appear as faults, resulting in a sharp increase in the internal resistance of the battery. Although introducing acrylate comonomers into PVDF can moderately improve the adhesion strength between the separator and the electrode sheet, it is still difficult to meet the actual requirements. In addition, PVDF swells significantly in strongly polar electrolytes, which will significantly weaken the wet adhesion force between the separator and the electrode sheet; and, with the progress of cycling, the swollen PVDF is prone to migrate to the edge of the battery, and ultimately leads to the overflow of PVDF, which not only affects the interface stability, but also accelerates the decay of battery performance.

[0004] In view of this, the present invention is specifically proposed. Summary of the Invention

[0005] The purpose of the present invention is to provide a porous composite separator, a preparation method thereof, and a secondary battery. The porous composite separator of the present invention can improve the adhesion performance with the electrode sheet while enhancing the lithium-ion conductivity.

[0006] To achieve the above object of the present invention, the first aspect of the present invention provides a porous composite separator, including a base film, a first coating, and a second coating; the first coating and the second coating are oppositely arranged on both sides of the base film; The first coating and the second coating each independently include a copolymer containing a first monomer unit and a second monomer unit; the first monomer unit contains a cyano group on the side chain, and the second monomer unit contains a carbonyl group on the side chain; in the copolymer, the molar proportion of the second monomer unit is 1% - 20%; The first coating and the second coating each independently include a framework structure and a first type of pore structure formed between the framework structures, and a second type of pore structure is formed on the body of the framework structure; the average pore diameter of the first type of pore structure is larger than the average pore diameter of the second type of pore structure.

[0007] In some embodiments, in the copolymer, the molar proportion of the second monomer unit is 8% to 20%.

[0008] In some embodiments, the first monomer unit is derived from acrylonitrile, and the second monomer unit is derived from an unsaturated carbonyl compound. Further, the unsaturated carbonyl compound includes at least one of acrylate monomers, acrylic monomers, and acrylamide monomers.

[0009] In some embodiments, the acrylate monomers include at least one of methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate.

[0010] In some embodiments, the acrylic monomers include (meth)acrylic acid.

[0011] In some embodiments, the acrylamide monomers include at least one of acrylamide, diacetone acrylamide, and N-methylol acrylamide.

[0012] In some embodiments, the unsaturated carbonyl compound includes: (i) acrylate monomers; and, (ii) at least one of acrylic monomers and acrylamide monomers.

[0013] In some embodiments, the weight-average molecular weight of the copolymer is 200,000 to 1,000,000, and the glass transition temperature Tg of the copolymer is 40 to 120 °C.

[0014] In some embodiments, the average pore diameter of the first type of pore structure is 1 to 8 μm, and the average pore diameter of the second type of pore structure is 30 to 150 nm.

[0015] In some embodiments, in any 25.6 μm × 19.2 μm field of view of the first coating and the second coating, the number of the first type of pore structures is 40 to 120.

[0016] In some embodiments, the first coating and the second coating are scanned and imaged using a scanning electron microscope (SEM) to obtain SEM secondary electron images. Based on the SEM secondary electron images, the edges of the first type of pore structure are fitted into a two-dimensional graph. The lengths of the longest line segment and the shortest line segment that pass through the geometric center of the two-dimensional graph and intersect with the two-dimensional graph are set as M and N respectively, where M < 15 μm and 0.2 ≤ N / M ≤ 1.

[0017] In some embodiments, the direction from the first coating to the base film and perpendicular to the base film is set as the first direction. The height difference between the highest point and the lowest point of the first type of pore structure in the first direction is h, and h is 0.1 - 4 μm.

[0018] In some embodiments, under the condition of 25 °C, the porous composite separator is pressurized for 5 min. The change value Δh of h before and after pressurization and the pressure P during pressurization satisfy: 0.01 ≤ Δh / P ≤ 0.2; where P is 0.1 - 20 MPa.

[0019] In some embodiments, the areal densities of the first coating and the second coating are each independently 0.1 - 3 g / m 2 。

[0020] In some embodiments, the first coating and the second coating each independently include an inorganic heat-resistant material. Further, the inorganic heat-resistant material includes at least one of alumina, boehmite, barium sulfate, barium titanate, magnesium hydroxide, and silica.

[0021] In some embodiments, in the first coating and the second coating, the mass ratio of the copolymer to the inorganic heat-resistant material is each independently 1:(0.5 - 2).

[0022] In some embodiments, the porous composite separator further includes a heat-resistant coating, and the heat-resistant coating is disposed between the base film and the first coating.

[0023] In some embodiments, the heat-resistant coating includes inorganic heat-resistant particles and a binder polymer; the inorganic heat-resistant particles include at least one of alumina, boehmite, barium sulfate, barium titanate, magnesium hydroxide, and silica, and the D50 particle size of the inorganic heat-resistant particles is 1 - 1.5 μm.

[0024] In some embodiments, the base film includes at least one of a polyethylene base film and a polypropylene base film.

[0025] The second aspect of the present invention provides a method for preparing the porous composite separator provided in the first aspect of the present invention, comprising the following steps: preparing a slurry for the first coating and a slurry for the second coating, respectively coating the slurry for the first coating and the slurry for the second coating on both sides of a base film, then immersing it in a coagulation bath, and then performing a drying treatment.

[0026] The second aspect of the present invention provides another method for preparing the porous composite separator provided in the first aspect of the present invention, comprising the following steps: (a) Preparing a slurry for a heat-resistant coating, coating the slurry for the heat-resistant coating on one side of a base film, and performing a drying treatment to form a heat-resistant coating; (b) Preparing a slurry for the first coating and a slurry for the second coating, respectively coating the slurry for the first coating and the slurry for the second coating on both sides of the base film formed with the heat-resistant coating, then immersing it in a coagulation bath, and then performing a drying treatment.

[0027] In some embodiments, the coagulation bath includes a primary coagulation bath, a secondary coagulation bath, and a tertiary coagulation bath; the primary coagulation bath, the secondary coagulation bath, and the tertiary coagulation bath are all aqueous solutions of N,N-dimethylacetamide, and the concentration of N,N-dimethylacetamide decreases in sequence. Further, the concentrations of N,N-dimethylacetamide in the primary coagulation bath, the secondary coagulation bath, and the tertiary coagulation bath are 55 wt% - 65 wt%, 8 wt% - 12 wt%, and 3 wt% - 7 wt%, respectively.

[0028] The third aspect of the present invention provides a secondary battery, comprising the porous composite separator described in the first aspect of the present invention.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) In the porous composite separator of the present invention, a copolymer with a cyano group and a carbonyl group in the side chain is used as a binder component. The cyano group of the first monomer unit forms an intermolecular interaction network through hydrogen bonding and dipole interaction, endowing it with excellent oxidation resistance; the introduction of the second monomer unit appropriately reduces the regularity of the molecular chain formed by the first monomer unit, which not only enables the copolymer to have good dispersibility and solubility in the solvent, helps to form a uniform and stable coating structure, but also can improve the adhesion performance between the coating and the electrode sheet containing the active material; (2) In the porous composite separator of the present invention, a first type of pore structure and a second type of pore structure with different pore diameters are provided in the first coating and the second coating. The dual-scale pore structure forms a continuous network structure, which is more conducive to the transmission of lithium ions and improves the lithium ion conduction performance; (3) In the porous composite separator of the present invention, the dimensions of the first type of pore structure in the first coating and the second coating in the thickness direction are further adjusted to form a certain liquid retention area between the separator and the electrode, which helps the liquid retention ability under high voltage / high viscosity and other conditions, and improves the rate cycling performance of the battery cell. (4) The secondary battery of the present invention has excellent cycle stability and rate performance. Description of the Drawings

[0030] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the description of the specific embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0031] Figure 1 It is a schematic structural diagram of a porous composite separator provided by the present invention; Figure 2 It is a schematic structural diagram of another porous composite separator provided by the present invention; Figure 3 It is an SEM image of the surface of the second coating of the porous composite separator prepared in Example 1 of the present invention; Figure 4 It is an SEM image of the surface of the second coating of the porous composite separator prepared in Example 1 of the present invention at another magnification; Figure 5 It is a picture of the SEM image of the surface of the second coating of Example 1 of the present invention adjusted by ImageJ; Figure 6 It is a cross-sectional SEM of the second coating of the porous composite separator prepared in Example 1 of the present invention.

[0032] Reference Numerals: 10 - base film; 20 - first coating; 30 - second coating; 40 - heat-resistant coating. Specific Embodiments

[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the following described embodiments are part of the embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work fall within the scope of protection of the present invention. For those conditions not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. For reagents or instruments whose manufacturers are not specified, they are all conventional products that can be obtained through commercial purchase.

[0034] In the description of the present invention, it should be noted that the orientation or positional relationship indicated by the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc. is based on the orientation or positional relationship shown in the accompanying drawings. It is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be construed as limiting the present invention. In addition, the terms "first", "second", "third" are only used for descriptive purposes and cannot be construed as indicating or implying relative importance.

[0035] Figure 1 The following is a schematic structural diagram of a porous composite separator provided by the present invention. In the first aspect of the present invention, a porous composite separator is provided, including a base film 10, a first coating 20, and a second coating 30; the first coating 20 and the second coating 30 are oppositely arranged on both sides of the base film 10; The first coating 20 and the second coating 30 each independently include a copolymer containing a first monomer unit and a second monomer unit; the first monomer unit contains a cyano group in the side chain, and the second monomer unit contains a carbonyl group in the side chain; in the copolymer, the molar proportion of the second monomer unit is 1% to 20%; The first coating and the second coating each independently include a skeleton structure and a first type of pore structure formed between the skeleton structures, and a second type of pore structure is formed on the body of the skeleton structure; the average pore diameter of the first type of pore structure is larger than the average pore diameter of the second type of pore structure.

[0036] In the porous composite separator of the present invention, a copolymer with cyano and carbonyl groups in the side chain is used as the bonding component. The cyano groups of the first monomer unit form an intermolecular interaction network through hydrogen bonds and dipole interactions, endowing it with excellent oxidation resistance; the introduction of the second monomer unit appropriately reduces the regularity of the molecular chain formed by the first monomer unit, which not only enables the copolymer to have good dispersibility and solubility in solvents, helps to form a uniform and stable coating structure, but also can improve the bonding performance between the coating and the electrode sheet containing the active material. The first coating and the second coating of the present invention can be the same or different.

[0037] The higher the content of cyano groups in the copolymer, the higher the proportion of the intermolecular interaction network formed by cyano groups through hydrogen bonding and dipole-dipole interaction, the stronger the rigidity of the copolymer, which is beneficial to the improvement of oxidation resistance. However, if the rigidity of the copolymer is too strong, the molecular chain movement is restricted and the flexibility becomes poor, making it difficult to fully wet the electrode to be bonded, thus affecting the bonding performance. In the present invention, by introducing a certain amount of the second monomer unit into the copolymer, the crystalline region formed by the first monomer unit is moderately disrupted, the bonding performance of the copolymer is improved, and the temperature and pressure ranges for realizing bonding are broadened, which is beneficial to actual production. In the present invention, the molar proportion of the second monomer unit in the copolymer is controlled to be 1% - 20% to balance the oxidation resistance and bonding performance of the copolymer. For example, in different embodiments, the molar proportion of the second monomer unit in the copolymer can be 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20% or the range composed of any two of them. The molar proportion of the second monomer unit in the copolymer of the present invention is obtained by nuclear magnetic characterization and calculation of the copolymer.

[0038] In the porous composite separator of the present invention, the first type of pore structure and the second type of pore structure with different pore diameters are provided in the first coating and the second coating. The dual-scale pore structure forms a continuous network structure, which is more conducive to the transport of lithium ions and improves the lithium ion conduction performance. Among them, the main body of the framework structure includes the inside and the surface of the framework structure body.

[0039] In some embodiments, the first monomer unit is derived from acrylonitrile and the second monomer unit is derived from an unsaturated carbonyl compound. Further, the unsaturated carbonyl compound includes at least one of acrylate monomers, acrylic monomers, and acrylamide monomers.

[0040] Among them, the first monomer unit is derived from acrylonitrile and the second monomer unit is derived from an unsaturated carbonyl compound means that a copolymer containing the first monomer unit and the second monomer unit is obtained by copolymerizing acrylonitrile and an unsaturated carbonyl compound.

[0041] In some embodiments, in the copolymer, the nitrogen element content is 15wt% - 26wt%, for example, it can be 15wt%, 16wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt% or the range composed of any two of them. The nitrogen element in the copolymer is mainly provided by cyano groups. Controlling the nitrogen element content in the copolymer within the above range is more helpful to provide appropriate rigidity, thereby improving the oxidation resistance; and avoiding the deterioration of bonding performance caused by too high cyano group content.

[0042] In some embodiments, the acrylate monomers include at least one of methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate.

[0043] In some embodiments, the acrylic monomer includes (meth)acrylic acid.

[0044] In some embodiments, the acrylamide monomer includes at least one of acrylamide, diacetone acrylamide, and N-methylol acrylamide.

[0045] In some embodiments, the unsaturated carbonyl compound includes: (i) acrylate monomers; and (ii) at least one of acrylic monomers and acrylamide monomers.

[0046] Introducing acrylic monomers and / or acrylamide monomers into the unsaturated carbonyl compound of the present invention is more helpful for improving the dispersibility, solubility, and adhesion performance of the copolymer.

[0047] In some embodiments, in the unsaturated carbonyl compound, the molar proportion of acrylate monomers is 90% - 99%, for example, it can be 90%, 92%, 95%, 97%, 99% or the range composed of any two of them, and the total molar proportion of acrylic monomers and acrylamide monomers is 1% - 10%, for example, it can be 1%, 3%, 5%, 8%, 10% or the range composed of any two of them.

[0048] In some embodiments, the weight-average molecular weight (Mw) of the copolymer is 200,000 - 1,000,000, for example, it can be 200,000, 350,000, 500,000, 650,000, 800,000, 1,000,000 or the range composed of any two of them, for example, it can be 300,000 - 650,000; the glass transition temperature Tg of the copolymer is 40 - 120 °C, for example, it can be 40 °C, 50 °C, 60 °C, 80 °C, 100 °C, 120 °C or the range composed of any two of them, for example, it can be 60 - 100 °C. Adjusting the molecular chain of the copolymer and the glass transition temperature within the above range is more helpful for taking into account the improvement of the oxidation resistance of the coating and the adhesion performance to the electrode sheet.

[0049] In some embodiments, the copolymer is mainly prepared by polymerizing acrylonitrile and an unsaturated carbonyl compound. Further, the polymerization is carried out in water under the initiation of an initiator.

[0050] In some embodiments, the initiator includes but is not limited to persulfates, such as ammonium persulfate. The dosage of the initiator can be 0.1% - 0.5% of the total mass of the monomers used in the polymerization.

[0051] In actual operation, the amount of water used in the polymerization is determined to ensure the stable progress of the polymerization reaction. For example, it can be 0.5 - 2 times the total mass of the monomers used in the polymerization. In some embodiments, after the polymerization is completed, the copolymer powder is obtained by spray drying.

[0052] In some embodiments, a chain transfer agent is further included in the polymerization system. The chain transfer agent includes, but is not limited to, mercaptan-based chain transfer agents such as dodecyl mercaptan. The dosage of the chain transfer agent can be 0.01% to 1% of the total mass of the monomers used in the polymerization, and can be routinely adjusted according to the target molecular weight of the copolymer.

[0053] In some embodiments, the polymerization temperature is 60 to 80 °C, but is not limited thereto, as long as it can initiate the polymerization of the monomers. The polymerization time can be 24 to 48 h, but is not limited thereto, and can be routinely adjusted according to the target molecular weight of the copolymer.

[0054] In some embodiments, the average pore diameter of the first type of pore structure is 1 to 8 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or a range composed of any two of them. The average pore diameter of the second type of pore structure is 30 to 150 nm, for example, it can be 30 nm, 40 nm, 50 nm, 60 nm, 80 nm, 100 nm, 120 nm, 150 nm, or a range composed of any two of them.

[0055] In some embodiments, within any 25.6 μm × 19.2 μm field of view of the first coating and the second coating, the number of the first type of pore structures is independently 40 to 120, for example, it can be 40, 60, 80, 100, 120, or a range composed of any two of them, which is more conducive to improving the adhesion performance and liquid retention performance. Among them, the number of the first type of pore structures within the 25.6 μm × 19.2 μm field of view is obtained by scanning the surface images of the first coating and the second coating with a scanning electron microscope and counting. Specifically, the counting method includes: using ImageJ to adjust the picture threshold range of the surface image (0 ≤ MinThr ≤ 10, 60 ≤ MaxThr ≤ 150, for example, MinThr is 7 and MaxThr is 115) to make the edges of the first type of pore structures in the picture prominent, using the software to draw along the contour of the pore structures (specifically draw along the part with higher gray value, which appears white or nearly white), obtaining the drawn image, and counting the smallest unit in the drawn image as 1 pore structure, and also counting the smallest unit that is not fully displayed at the edge of the drawn image as 1 pore structure.

[0056] In some embodiments, the first coating and the second coating are scanned and imaged using SEM to obtain SEM secondary electron images. Based on the SEM secondary electron images, the edges of the first type of pore structure are fitted into two-dimensional graphics. The lengths of the longest line segment and the shortest line segment that are set to pass through the geometric center of the two-dimensional graphics and intersect the two-dimensional graphics are M and N, respectively. M < 15 μm, and 0.2 ≤ N / M ≤ 1. For example, N / M can be 0.2, 0.4, 0.5, 0.6, 0.8, 1, or a range composed of any two of them. The first type of pore structure that satisfies the above conditions is more conducive to fully exerting the lithium-ion transport performance and the liquid retention ability. Among them, the drawn image is obtained according to the statistical method of the number of the first type of pore structure, and the maximum Feret diameter MaxFeret and the minimum Feret diameter MinFeret of the two-dimensional graphics fitted by the edges of each first type of pore structure in the drawn image are measured using ImageJ software, which are M and N.

[0057] In some embodiments, the direction from the first coating to the base film and perpendicular to the base film is set as the first direction. The height difference h between the highest point and the lowest point of the first type of pore structure in the first direction is 0.1 to 4 μm. For example, it can be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or a range composed of any two of them.

[0058] In the porous composite separator of the present invention, the dimensions of the first type of pore structure in the thickness direction of the first coating and the second coating are further adjusted to form a certain liquid retention area between the separator and the electrode sheet, which is conducive to the liquid retention ability under conditions such as high voltage / high viscosity, and improves the rate cycling performance of the battery cell.

[0059] In some embodiments, the porous composite separator is pressurized at 25 °C for 5 minutes. The change value Δh of h before and after pressurization and the pressure P applied satisfy: 0.01 ≤ Δh / P ≤ 0.2; where P is 0.1 to 20 MPa. Further, the pressurization is to apply a constant pressure.

[0060] It should be noted that when calculating Δh / P, the units represented by Δh and P are not considered, and only the corresponding values when the unit of Δh is μm and the unit of P is MPa are used to calculate the results corresponding to the relevant relationships.

[0061] For example, in different embodiments, under the above test conditions, Δh / P of the porous composite separator of the present invention can be 0.01, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, or a range composed of any two of them, indicating that the porous composite separator of the present invention has a relatively stable structure, is not easily deformed under external forces after being applied to the battery cell, and can ensure the lithium-ion transport.

[0062] In some embodiments, the first coating and the second coating each independently comprise an inorganic heat-resistant material. Further, the inorganic heat-resistant material comprises at least one of alumina, boehmite, barium sulfate, barium titanate, magnesium hydroxide, and silica; the D50 particle size of the inorganic heat-resistant material is 0.01 - 800 nm, for example, it can be 0.01 nm, 0.1 nm, 1 nm, 10 nm, 50 nm, 100 nm, 300 nm, 500 nm, 600 nm, 800 nm, or a range composed of any two of them. Further introducing the inorganic heat-resistant material into the first coating and the second coating is more helpful for improving the thermal stability of the separator and ensuring battery safety.

[0063] In some embodiments, in the first coating and the second coating, the mass ratio of the copolymer to the inorganic heat-resistant material is each independently 1:(0.5 - 2), for example, it can be 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, or a range composed of any two of them.

[0064] In some embodiments, the areal density of the first coating and the second coating is each independently 0.1 - 3 g / m 2 , for example, it can be 0.1 g / m 2 , 0.5 g / m 2 , 0.8 g / m 2 , 1 g / m 2 , 1.5 g / m 2 , 2 g / m 2 , 2.5 g / m 2 , 3 g / m 2 or a range composed of any two of them. A suitable areal density is more helpful for balancing the separator strength, lithium-ion transmission ability, and adhesion strength, etc.

[0065] Figure 2 FIG. is a schematic structural diagram of another porous composite separator provided by the present invention. The porous composite separator further comprises a heat-resistant coating 40, and the heat-resistant coating 40 is disposed between the base film 10 and the first coating 20. Specifically, the porous composite separator comprises a base film 10, a heat-resistant coating 40 disposed on one surface of the base film 10, a first coating 20 disposed on the surface of the heat-resistant coating 40, and a second coating 30 disposed on the other surface of the base film 10.

[0066] In some embodiments, the heat-resistant coating comprises inorganic heat-resistant particles and a binder polymer; the inorganic heat-resistant particles comprise at least one of alumina, boehmite, barium sulfate, barium titanate, magnesium hydroxide, and silica, and the D50 particle size of the inorganic heat-resistant particles is 1 - 1.5 μm, for example, it can be 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, or a range composed of any two of them.

[0067] In some embodiments, the adhesive polymer includes at least one of styrene-butadiene rubber, polymethyl methacrylate, polybutyl methacrylate, polyacrylic acid, polymethacrylic acid, polyacrylamide, and acrylonitrile-acrylic acid copolymer.

[0068] In some embodiments, in the heat-resistant coating, the mass ratio of the inorganic heat-resistant particles to the adhesive polymer is (2-4):1. For example, it can be 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, 3.2:1, 3.5:1, 3.8:1, 4:1, or the range composed of any two of them.

[0069] In some embodiments, the heat-resistant coating further includes at least one of a thickening agent and a dispersing agent. Auxiliaries such as thickening agents and dispersing agents can be selectively added according to the actual process conditions, and the addition amounts can be adjusted conventionally, which will not be elaborated here.

[0070] In some embodiments, the thickness of the heat-resistant coating is 0.1-3 μm. For example, it can be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, or the range composed of any two of them.

[0071] In some embodiments, the base film includes at least one of a polyethylene film and a polypropylene film. Further, the thickness of the base film is 3-10 μm. Specifically, the base film can be a porous base film.

[0072] The second aspect of the present invention provides a method for preparing the porous composite separator provided in the first aspect of the present invention, including the following steps: preparing the slurry of the first coating and the slurry of the second coating, respectively coating the slurry of the first coating and the slurry of the second coating on both sides of the base film, then immersing them in a coagulation bath, and then performing a drying treatment.

[0073] The second aspect of the present invention provides another method for preparing the porous composite separator provided in the first aspect of the present invention, including the following steps: (a) Preparing the slurry of the heat-resistant coating, coating the slurry of the heat-resistant coating on one side of the base film, and performing a drying treatment to form a heat-resistant coating; (b) Preparing the slurry of the first coating and the slurry of the second coating, respectively coating the slurry of the first coating and the slurry of the second coating on both sides of the base film formed with the heat-resistant coating, then immersing them in a coagulation bath, and then performing a drying treatment.

[0074] In actual operation, the coating methods for the slurry of the first coating, the slurry of the second coating, and the slurry of the heat-resistant coating may include, but are not limited to, microgravure roll coating. Further, during coating, the relative environmental humidity RH is 10% to 70%, for example, it can be 10%, 20%, 40%, 50%, 60%, 70%, or the range composed of any two of them. In the subsequent embodiments, the relative environmental humidity during coating is 50% ± 2%.

[0075] The slurries of the first coating, the second coating, and the heat-resistant coating can be prepared by conventional stirring according to the composition of their respective coatings. For example, the slurries of the first coating and the second coating each independently include a copolymer, a solvent, and optionally an inorganic heat-resistant material. Among them, the dosage of the solvent can be conventionally adjusted according to the solubility of the copolymer and the coating performance of the slurry to ensure that the copolymer is dissolved and an appropriate viscosity is obtained, so as to provide good coating performance. The types of solvents include, but are not limited to, N,N-dimethylacetamide.

[0076] When the first coating and the second coating of the first porous composite separator do not contain inorganic heat-resistant materials, then inorganic heat-resistant materials are not added to the slurries of the first coating and the second coating; when the first coating and the second coating of the first porous composite separator contain inorganic heat-resistant materials, then inorganic heat-resistant materials are added to the slurries of the first coating and the second coating, and the specific addition amount is adjusted according to the content of the inorganic heat-resistant materials in the first coating and the second coating; for example, when preparing the slurries of the first coating and the second coating, the mass ratio of the copolymer to the inorganic heat-resistant material can be controlled to be 1﹕(0.5 - 2).

[0077] In some embodiments, when the porous composite separator contains a heat-resistant coating, the slurry of the heat-resistant coating includes inorganic heat-resistant particles, a binder polymer, and optionally a thickener and optionally a dispersant. Among them, the binder polymer is added in the form of a liquid such as an emulsion, a solution, a dispersion, etc., and the solid content can be conventionally adjusted according to the actual situation to ensure the uniformity and coatability of the slurry; the thickeners include, but are not limited to, carboxymethyl cellulose, guar gum, polyacrylamide, etc., and the dosage of the thickener can be 0% to 15% of the mass of the solid content of the binder polymer; the dispersants include, but are not limited to, ammonium polyacrylate, polyethylene glycol, polyvinylpyrrolidone, etc., and the dosage of the dispersant can be 0% to 15% of the mass of the solid content of the binder polymer.

[0078] In some embodiments, the coagulation bath includes a primary coagulation bath, a secondary coagulation bath, and a tertiary coagulation bath; the primary coagulation bath, the secondary coagulation bath, and the tertiary coagulation bath are all aqueous solutions of N,N-dimethylacetamide, and the concentration of N,N-dimethylacetamide decreases in sequence.

[0079] In the preparation of the porous composite separator of the present invention, after coating the first coating and the second coating, it is immersed in a coagulation bath. By using the exchange between the solvent and the non-solvent and cooperating with the copolymer composition, a suitable pore structure is formed. At the same time, the concentration of N,N-dimethylacetamide in the coagulation bath is regulated. First, it passes through a primary coagulation bath with a high concentration of N,N-dimethylacetamide, which helps to form small and uniform second-type pore structures; then the concentration of N,N-dimethylacetamide in the subsequent coagulation baths is gradually decreased in turn, the water content is increased, the phase separation speed is increased, and the formation of the first-type pore structures with larger pore diameters is promoted. Thus, a dual-scale pore structure is formed, improving the lithium ion conduction performance.

[0080] In some embodiments, the concentrations of N,N-dimethylacetamide in the primary coagulation bath, the secondary coagulation bath, and the tertiary coagulation bath are 55wt% - 65wt%, 8wt% - 12wt%, and 3wt% - 7wt% respectively. This is more conducive to forming the first-type pore structures and the second-type pore structures with appropriate sizes and quantities, further improving the lithium ion conduction performance and liquid retention capacity of the separator, etc.

[0081] In some embodiments, the drying treatment includes: drying at 50 - 80°C. The specific drying method can include but is not limited to drying by baking.

[0082] The third aspect of the present invention provides a secondary battery, including the porous composite separator of the first aspect of the present invention. The secondary battery assembled with the porous composite separator of the present invention has excellent cycle stability and rate performance.

[0083] In some embodiments, the secondary battery further includes a positive electrode sheet, a negative electrode sheet, and an electrolyte. The positive electrode active material of the positive electrode sheet can include but is not limited to a high-nickel ternary positive electrode material; the negative electrode active material of the negative electrode sheet can include but is not limited to a silicon-carbon negative electrode material; the electrolyte can include a commercial liquid electrolyte.

[0084] The adhesion between the porous composite separator of the present invention and the positive electrode sheet is 10 - 40N / m, and can be, for example, 10N / m, 15N / m, 20N / m, 25N / m, 30N / m, 35N / m, 40N / m, or the range composed of any two of them.

[0085] In the following embodiments, the case where the first coating and the second coating are the same is taken as an example for illustration, rather than limiting that the first coating and the second coating must be the same; it can be understood that embodiments where the first coating and the second coating are different and each meets the conditions defined in the present invention also fall within the protection scope of the present invention. In addition, in the following embodiments, the slurries used to prepare the first coating and the second coating are the same, and the surface density of the second coating, the size and quantity of the first type of pore structure, the size and quantity of the second type of pore structure, the adhesion to the positive electrode sheet, etc. are characterized. For the relevant parameters of the first coating, they are the same as or within an acceptable deviation range of the parameters of the second coating. For example, the acceptable deviation range is within ±5% of the parameters of the second coating.

[0086] Example 1 This example provides a method for preparing a porous composite separator, which includes the following steps: (1) Add 502 g of butyl acrylate, 1511 g of acrylonitrile, and 8 g of acrylic acid into a reaction kettle containing 2 kg of deionized water, heat up to 70 °C, stir evenly, and then gradually add 12 g of ammonium persulfate and 20 g of n-dodecyl mercaptan, and react for 36 h to obtain an emulsion. Spray-dry the emulsion to obtain copolymer powder.

[0087] (2) Add 1 kg of N,N-dimethylacetamide into a 2 L stirring kettle, add 40 g of copolymer powder, stir at a stirring speed of 1500 rpm at 25 °C for 4 h to obtain a copolymer solution. Then add 40 g of alumina particles with a D50 particle size of 0.34 μm, and continue to stir for 1 h to obtain a ceramic copolymer mixture.

[0088] (3) Add 13.5 g of alumina particles with a D50 particle size of 0.92 μm into a 1 L stirring kettle, add 0.5 g of ammonium polyacrylate, 0.8 g of sodium carboxymethylcellulose, and 20 g of a polyacrylic acid solution with a solid content of 25%, and stir at a stirring speed of 1000 rpm at 25 °C for 4 h to obtain an alumina particle dispersion.

[0089] (4) Coat the alumina particle dispersion on the surface of one side of a polyethylene film with a thickness of 5 μm through a microgravure roll coater, and dry it in an oven at 60-65 °C to obtain a heat-resistant coating with a thickness of 1 μm.

[0090] (5) The ceramic copolymer mixture is coated on the surface of the other side of the polyethylene film treated in step (4) and the surface of the heat-resistant coating by microgravure roll coating, and then successively passed through an aqueous solution of N,N-dimethylacetamide with a concentration of 60 wt%, an aqueous solution of N,N-dimethylacetamide with a concentration of 10 wt%, and an aqueous solution of N,N-dimethylacetamide with a concentration of 5 wt%. The coagulation time for each N,N-dimethylacetamide aqueous solution is 60 s; then it is dried in an oven at 60-65 °C to obtain a porous composite separator; wherein, the areal density of the first coating on the surface of the heat-resistant coating and the second coating on the surface of the polyethylene film is both 1.69 g / m 2 .

[0091] Figure 3 FIG. Figure 4 FIG. is the SEM image of the surface of the second coating of the porous composite separator prepared in this example. As can be seen from the figure, the second coating includes a framework structure and a first type of pore structure formed between the framework structures, and a second type of pore structure is formed on the body of the framework structure.

[0092] Examples 2-6 Examples 2-6 refer to the preparation method of the porous composite separator in Example 1, the difference is that: the dosage of the monomers used to prepare the copolymer in step (1) is different, and the areal density of the first coating / second coating in step (5) is different. The specific differences are shown in Table 1.

[0093] Table 1 Monomer dosage and coating areal density in step (1) of Examples 2-6

[0094] Example 7 Example 7 refers to the preparation method of the porous composite separator in Example 1, the difference is that: step (2) is different.

[0095] Step (2) of this example includes: adding 1 kg of N,N-dimethylacetamide to a 2 L stirring kettle, adding 80 g of copolymer powder, and stirring at a stirring speed of 1500 rpm at 25 °C for 4 h to obtain a copolymer solution. In the corresponding step (5), the copolymer solution is used to replace the ceramic copolymer mixture in Example 1; the areal density of the first coating and the second coating is both 0.71 g / m 2 .

[0096] Comparative Examples 1-8 Comparative Examples 1-8 refer to the preparation method of the porous composite separator in Example 1, the difference is that: the dosage of the monomers used to prepare the copolymer in step (1) is different, and the areal density of the first coating / second coating in step (5) is different. The specific differences are shown in Table 1.

[0097] Table 2 Monomer dosage information in step (1) of Comparative Examples 1-8

[0098] Comparative Example 9 Comparative Example 9 refers to the preparation method of the porous composite separator in Example 1, except that: a PVDF ceramic mixed solution is used to replace the ceramic copolymer mixed solution in Example 1, and the porous composite separator is prepared according to the methods in steps (3)-(5). In step (5), the areal density of both the first coating and the second coating is 1.68 g / m 2 .

[0099] Among them, the preparation of the PVDF ceramic mixed solution includes: adding 1 kg of N,N-dimethylacetamide to a 2 L stirring kettle, adding 40 g of PVDF resin (containing 4 mol% HFP, specifically it can be Heverfluororesin Co., Ltd., grade HEVER2601), stirring at 25 °C at a stirring speed of 1500 rpm for 4 h to obtain a PVDF resin solution. Then add 40 g of alumina particles with a D50 particle size of 0.34 μm and continue to stir for 1 h to form a PVDF ceramic mixed solution.

[0100] Experimental Example I. Detection of monomer ratio in the copolymer Dissolve the copolymer powder in dimethyl sulfoxide and measure respectively 13 C-NMR, 1 H-NMR, and calculate the molar proportion of unsaturated carbonyl compounds in the copolymer according to the test results.

[0101] II. Detection of nitrogen element content in the copolymer EDS test method: Use a Japanese electron scanning electron microscope for testing, the electron microscope model is IT800, and the energy spectrum EDS model is Oxford AZtecLive UltimMax 65. Specifically, take a conductive adhesive with a length × width = 30 mm × 8 mm and paste it on the sample holder, place the copolymer powder on the surface of the conductive adhesive, and perform gold spraying treatment in an ion sputtering instrument (current 20 mA, time 45 s); use a working distance of 8 mm, a working voltage of 15 kv, and a beam current of 50 nA to perform EDS point scanning on the sample for focusing, collect and analyze the spectrum of the scanned image, and calculate the nitrogen element content.

[0102] III. Detection of the weight-average molecular weight of the copolymer Dissolve the copolymer powder in N,N-dimethylformamide, and use a gel permeation chromatograph (PL-GPC50) equipped with 2 x PLgel Mixed-B 7.5 × 300 mm chromatographic columns to detect through a differential refractive index detector at 50 °C.

[0103] IV. Detection of the glass transition temperature Tg of the copolymer Using differential scanning calorimetry, weigh 5 - 10 mg of the copolymer powder to be tested with a 40 μL aluminum crucible, select a nitrogen test atmosphere, with a temperature test range of -80 to 300 °C, heat at a rate of 10 °C / min, obtain a curve, and analyze to obtain the glass transition temperature Tg.

[0104] V. Test for the adhesion between the second coating and the positive electrode sheet containing the active material 1. Stir and mix the positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF evenly in an appropriate amount of N-methylpyrrolidone according to a weight ratio of 97:1.5:1.5, and then coat it on the positive electrode current collector aluminum foil, dry and cold press to obtain the positive electrode sheet; 2. Cut the positive electrode sheet and the porous composite diaphragm to be tested, both with a size of 41 mm × 60 mm, and stack them in alignment in the order of positive electrode sheet - porous composite diaphragm to be tested - polyethylene film - positive electrode sheet (the second coating of the porous composite diaphragm to be tested is in contact with the positive electrode sheet, and the first coating is in contact with the polyethylene film); then place it in a hot press and hot press for 5 min at 95 °C and 3 MPa to obtain the sample to be tested; 3. Peel the sample to be tested at 180°, with a peeling speed of 50 mm / min and a peeling length of 20 mm; the adhesion force F (N / m) = average value of the peeling force (N) / width of the sample to be tested (m).

[0105] VI. Average pore diameter of the first type of pore structure and average pore diameter of the second type of pore structure in the second coating Average pore diameter of the first type of pore structure: Parallelly take 5 samples of the porous composite diaphragm to be tested, and take the average value after testing by the following method. Respectively, under an SEM microscope, obtain 5KX magnification images on the side of the second coating, with a field of view range of 25.6 μm × 19.2 μm. Use ImageJ to adjust the picture threshold range of the surface image (MinThr is 7, MaxThr is 115) to make the edges of the first type of pore structure in the picture prominent, draw along the contour of the pore structure with a higher gray value to obtain a drawn image. The smallest unit in the drawn image is counted as 1 pore structure, and the smallest unit that is not fully displayed at the edge of the drawn image is also counted as 1 pore structure. Thus, the number n of the first type of pore structure within the 25.6 μm × 19.2 μm field of view is statistically obtained. Use ImageJ software to measure the area S of the two-dimensional image fitted by the edges of each first type of pore structure in the drawn graph, and then convert S into the equivalent diameter d of each first type of pore structure (the diameter of a circle equal to the area S); the average pore diameter d of the first type of pore structure n is calculated according to the following formula, and Σd is the sum of the equivalent diameters d of each first type of pore structure.

[0106]

[0107] Specifically, taking the porous composite separator prepared in Example 1 as an example, the picture obtained after adjusting the picture threshold of the surface image using ImageJ is as Figure 5 shown.

[0108] Average pore diameter of the second type of pore structure: Five samples of the porous composite separator to be tested are taken in parallel. After testing according to the following method, the average value is taken. Under the SEM microscope, 50KX magnification images of the second coating side are obtained respectively, and the field of view range is 2.56μm×1.92μm; the images are imported into the ImageJ software, and a drawing is made along the contour of the second type of pore structure to obtain a drawn image. The smallest unit in the drawn image is counted as 1 pore structure, and the smallest unit that is not fully displayed at the edge of the drawn image is also counted as 1 pore structure. Thus, the number n1 of the second type of pore structure within the field of view range of 2.56μm×1.92μm is statistically obtained. The ImageJ software is used to measure the area S1 of the two-dimensional figure fitted to the edge of each second type of pore structure in the drawn figure, and then the equivalent diameter d1 of each second type of pore structure is converted according to S1 (the diameter of a circle equal to the area S1); the average pore diameter d n1 of the second type of pore structure is calculated according to the following formula, and Σd1 is the sum of the equivalent diameters d1 of each second type of pore structure.

[0109]

[0110] VII. Determination of relevant parameters of the first type of pore structure in the second coating 1. Five samples of the porous composite separator to be tested are taken in parallel. Under the SEM microscope, 5KX magnification images of the second coating side are obtained respectively, and the field of view range is 25.6μm×19.2μm. The number n of the first type of pore structure in a single sample is obtained according to the method of the average pore diameter of the first type of pore structure above; then the average value is calculated according to the numbers counted from the 5 parallel samples.

[0111] 2. Height difference h: Using the ion polishing instrument IB-19530CP, the porous composite separator sample to be tested is cut under the conditions of voltage 3.5kV and time 4h; after cutting, the sample is sputter-coated with gold and photographed with an electron microscope (model IT800), and the field of view range is 16μm×12μm. The height difference h between the highest point and the lowest point of each first type of pore structure in the first direction is the height difference h. The average height difference of the first type of pore structure is calculated according to the following formula, Σh is the sum of the height differences of each first type of pore structure, and x is the number of the first type of pore structure within the field of view range of 16μm×12μm above.

[0112]

[0113] Specifically, taking the porous composite separator prepared in Example 1 as an example, the cross-sectional SEM of the second coating is as Figure 6 shown.

[0114] 3. △h / P: Test the height difference h of the porous composite separator to be tested according to the test method of the height difference h. Then, apply pressure to the porous composite separator to be tested at 25 °C and P = 7 MPa for 5 min, and test the height difference h1 of the porous composite separator to be tested after pressure application according to the test method of the height difference h. For each first-type pore structure, △h / P = (h - h1) / 7, and the average value of △h / P is △h / P / x.

[0115] 4. M and N: Under the SEM microscope, obtain a 5KX magnification image on the side of the second coating, with a field of view range of 25.6 μm × 19.2 μm. Obtain the drawn image and the number n of the first-type pore structures according to the method of the average pore diameter of the first-type pore structures. Use ImageJ software to measure the maximum Feret diameter MaxFeret and the minimum Feret diameter MinFeret of the two-dimensional figure fitted to the edge of each first-type pore structure in the drawn figure, which are M and N. Calculate the average values of M and N of the first-type pore structures according to the number n of the first-type pore structures within the above-mentioned field of view range.

[0116] VIII. Capacity Retention Rate of the Porous Composite Separator 1. Preparation of the positive electrode sheet: Stir and mix the positive electrode active material NCM811, conductive carbon black, and the binder PVDF evenly in an appropriate amount of N-methylpyrrolidone according to a weight ratio of 97:2:1 to form a positive electrode slurry. Then, coat it on both sides of the positive electrode current collector aluminum foil, dry, roll, and cut to obtain the positive electrode sheet; 2. Preparation of the negative electrode sheet: Stir and mix the negative electrode active material artificial graphite containing 10% silicon, sodium carboxymethylcellulose, and styrene-butadiene rubber evenly in an appropriate amount of deionized water according to a weight ratio of 97:1.5:1.5 to form a negative electrode slurry. Then, coat it on both sides of the negative electrode current collector copper foil, dry, roll, and cut to obtain the negative electrode sheet; 3. Stack the positive electrode sheet, the porous composite separator, and the positive electrode sheet in sequence, weld the tab, package the aluminum-plastic film, pre-seal by hot pressing, inject the electrolyte (1 mol / L LiPF6, EC, PC, DEC, and EP with a volume ratio of 3:1:3:3), vacuum package, stand, hot press for formation, exhaust, and finally seal to obtain a lithium-ion battery.

[0117] 4. Capacity Retention Rate Test The lithium-ion battery was left standing at 25 °C for 30 min to reach a constant temperature state. It was charged at a constant current of 1C until the voltage reached 4.5V, and then charged at a constant voltage until the current reached 0.05C to make the lithium-ion battery reach a fully charged state. Then it was discharged at a constant current of 1C until the voltage reached 3.0V, and the discharge capacity at this time was recorded as C1; after 1000 cycles of charge and discharge, it was charged at a constant current of 0.5C until the voltage reached 4.5V, and then charged at a constant voltage until the current reached 0.05C to make the lithium-ion battery reach a fully charged state. Then it was discharged at a constant current of 1C until the voltage reached 3.0V, and the discharge capacity at this time was recorded as C2; then the discharge capacity retention rate after charging and discharging at 25 °C 1C / 1C = C2 / C1 × 100%.

[0118] The above test results are shown in Table 3 and Table 4.

[0119] Table 3 Test Result 1

[0120] Table 4 Test Result 2

[0121] Note: Having holes locally means that the pore formation is incomplete and closed pores appear.

[0122] In each embodiment of the present invention, the height difference h of a single first type of pore structure is in the range of 0.1 - 4 μm, M is less than 15 μm, and N / M is in the range of 0.2 - 1, and △h / P is in the range of 0.01 - 0.2.

[0123] In the porous composite separator of the present invention, a copolymer with a cyano group and a carbonyl group in the side chain is used as the bonding component. The cyano group of the first monomer unit forms an intermolecular interaction network through hydrogen bonds and dipole interactions, endowing it with excellent oxidation resistance; the introduction of the second monomer unit appropriately reduces the regularity of the molecular chain formed by the first monomer unit, which not only makes the copolymer have good dispersibility and solubility in the solvent, helps to form a uniform and stable coating structure, but also can improve the bonding performance between the coating and the electrode sheet containing the active material. Moreover, the first coating and the second coating contain first type of pore structures and second type of pore structures with different pore sizes, and the dual-scale pore structure forms a continuous network structure, which is more conducive to the transport of lithium ions and improves the lithium ion conduction performance. The first type of pore structure has a certain size in the thickness direction, which helps to form a certain liquid retention area between the separator and the electrode sheet, thereby improving the rate cycling performance of the battery cell.

[0124] Comparing Example 1, Comparative Example 1, and Comparative Examples 4 - 8, it can be seen that when the copolymer used in the first coating and the second coating does not contain acrylonitrile or the acrylonitrile content is too low, the rigidity of the copolymer is insufficient, not only the oxidation resistance is reduced, but also the sufficient bonding strength with the positive electrode sheet cannot be ensured.

[0125] Comparing Example 1 with Comparative Examples 2 to 3, it can be seen that when the amount of the unsaturated carbonyl compound part in the copolymer used for the first coating and the second coating is too small, the rigidity of the copolymer is too strong, making it difficult to wet the positive electrode sheet and affecting the bonding performance.

[0126] Comparing Example 1 with Comparative Example 9, it can be seen that when PVDF resin is used to prepare the first coating and the second coating, due to the insufficient rigidity of PVDF resin, the oxidation resistance cannot be guaranteed, and the bonding strength with the positive electrode sheet is insufficient.

[0127] At the same time, the copolymer compositions of Comparative Examples 1 to 9 result in the inability to form a dual-scale pore structure after coating and coagulation bath treatment, affecting the lithium ion transport performance.

[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements for some or all of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A porous composite separator, characterized in that, It includes a base film, a first coating, and a second coating; the first coating and the second coating are disposed opposite to each other on two sides of the base film; The first coating and the second coating each independently include a copolymer containing a first monomer unit and a second monomer unit; the first monomer unit contains a cyano group in the side chain, and the second monomer unit contains a carbonyl group in the side chain; in the copolymer, the molar proportion of the second monomer unit is 1% to 20%; The first coating and the second coating each independently include a framework structure and a first type of pore structure formed between the framework structures, and a second type of pore structure is formed on the body of the framework structure; the average pore diameter of the first type of pore structure is larger than the average pore diameter of the second type of pore structure.

2. The porous composite separator according to claim 1, wherein It has at least one of the following characteristics: (1) In the copolymer, the molar proportion of the second monomer unit is 8% to 20%; (2) The first monomer unit is derived from acrylonitrile; (3) The second monomer unit is derived from an unsaturated carbonyl compound; (4) The weight-average molecular weight of the copolymer is 200,000 to 1,000,000; (5) The glass transition temperature Tg of the copolymer is 40 to 120 °C.

3. The porous composite separator according to claim 2, wherein The unsaturated carbonyl compound includes at least one of acrylate monomers, acrylic monomers, and acrylamide monomers; The acrylate monomers include at least one of methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate; The acrylic monomers include (meth)acrylic acid; The acrylamide monomers include at least one of acrylamide, diacetone acrylamide, and N-methylol acrylamide.

4. The porous composite separator according to claim 1, wherein, It has at least one of the following characteristics: (1) The average pore diameter of the first type of pore structure is 1 to 8 μm; (2) The average pore diameter of the second type of pore structure is 30 to 150 nm; (3) In any 25.6 μm × 19.2 μm field of view of the first coating and the second coating, the number of the first type of pore structures is 40 to 120; (4) The first coating and the second coating are scanned and imaged by a scanning electron microscope to obtain an SEM secondary electron image. Based on the SEM secondary electron image, the edge of the first type of pore structure is fitted into a two-dimensional graph. The lengths of the longest line segment and the shortest line segment formed by setting a line passing through the geometric center of the two-dimensional graph and intersecting with the two-dimensional graph are set as M and N respectively. M < 15 μm, and 0.2 ≤ N / M ≤ 1.

5. The porous composite separator according to claim 1, characterized in that, It has at least one of the following characteristics: (1) Set the direction from the first coating to the base film and perpendicular to the base film as the first direction. The height difference between the highest point and the lowest point of the first type of pore structure in the first direction is h, and h is 0.1 to 4 μm; (2) Under the condition of 25 °C, the porous composite separator is pressurized for 5 minutes. The change value △h of h before and after pressurization and the pressure P of pressurization satisfy: 0.01 ≤ △h / P ≤ 0.2; where P is 0.1 to 20 MPa.

6. The porous composite separator according to claim 1, wherein It has at least one of the following characteristics: (1)The areal density of the first coating and the second coating are each independently 0.1 to 3 g / m 2 ; (2) The first coating and the second coating each independently include an inorganic heat-resistant material; (3) In the first coating and the second coating, the mass ratio of the copolymer to the inorganic heat-resistant material is independently 1:(0.5 - 2); (4) The base film includes at least one of a polyethylene base film and a polypropylene base film.

7. The porous composite separator according to claim 1 or 6, characterized in that, The porous composite separator further includes a heat-resistant coating disposed between the base film and the first coating; The heat-resistant coating includes inorganic heat-resistant particles and a binder polymer; the inorganic heat-resistant particles include at least one of alumina, boehmite, barium sulfate, barium titanate, magnesium hydroxide, and silica; The D50 particle size of the inorganic heat-resistant particles is 1 - 1.5 μm.

8. The preparation method of the porous composite separator according to any one of claims 1 to 6, characterized in that, It includes the following steps: preparing slurries for the first coating and the second coating, respectively coating the slurries for the first coating and the second coating on both sides of the base film, then immersing them in a coagulation bath, and then performing a drying treatment; The coagulation bath includes a primary coagulation bath, a secondary coagulation bath, and a tertiary coagulation bath; the primary coagulation bath, the secondary coagulation bath, and the tertiary coagulation bath are all aqueous solutions of N,N-dimethylacetamide, and the concentration of N,N-dimethylacetamide decreases in sequence.

9. The preparation method of the porous composite separator according to claim 7, characterized in that, It includes the following steps: (a) Preparing a slurry for the heat-resistant coating, coating the slurry for the heat-resistant coating on one side of the base film, and performing a drying treatment to form a heat-resistant coating; (b) Preparing slurries for the first coating and the second coating, respectively coating the slurries for the first coating and the second coating on both sides of the base film formed with the heat-resistant coating, then immersing them in a coagulation bath, and then performing a drying treatment; The coagulation bath includes a primary coagulation bath, a secondary coagulation bath, and a tertiary coagulation bath; the primary coagulation bath, the secondary coagulation bath, and the tertiary coagulation bath are all aqueous solutions of N,N-dimethylacetamide, and the concentration of N,N-dimethylacetamide decreases in sequence.

10. A secondary battery, characterized in that, It includes the porous composite separator according to any one of claims 1 - 7.

Citation Information

Patent Citations

  • High-heat-resistance lithium-ion battery diaphragm and preparation method thereof

    CN103531736A

  • Preparation method of high-performance inter-porous coated diaphragm

    CN105336901A

  • COMPOSITE diaphragm FOR SECONDARY BATTERY AND LITHIUM SECONDARY BATTERY CONTAINING SAME

    CN109841784A

  • Elastomer composite dot matrix coated composite diaphragm and lithium battery adopting diaphragm

    CN111785896A

  • Diaphragm and preparation method thereof, and battery

    CN112635918A

Cited By

  • Battery diaphragm, preparation method thereof and lithium battery

    CN121529114A

  • Battery separator, method for manufacturing the same, and lithium battery

    CN121529114B

  • Battery diaphragm, preparation method thereof and secondary battery

    CN121939092A